2017
DOI: 10.1371/journal.pone.0169291
|View full text |Cite
|
Sign up to set email alerts
|

p62 Pathology Model in the Rat Substantia Nigra with Filamentous Inclusions and Progressive Neurodegeneration

Abstract: One of the proteins most frequently found in neuropathological lesions is the ubiquitin binding protein p62 (sequestosome 1). Post-mortem analysis of p62 is a defining diagnostic marker in several neurodegenerative diseases including amyotrophic lateral sclerosis and inclusion body myositis. Since p62 functions in protein degradation pathways including autophagy, the build-up of p62-positive inclusions suggests defects in protein clearance. p62 was expressed unilaterally in the rat substantia nigra with an ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…8 One recent study has reported that p62 transfection resulted in mitochondrial dysfunction and progressive neurodegeneration in the rat brain. 9 Consistent with our previous results, 12 the current study also confirmed upregulated p62 levels in optic nerve degeneration, which was prevented by ripasudil. p62 may correlate with autophagic flux, and decreases in its level indicate autophagy induction while increases indicate autophagy inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…8 One recent study has reported that p62 transfection resulted in mitochondrial dysfunction and progressive neurodegeneration in the rat brain. 9 Consistent with our previous results, 12 the current study also confirmed upregulated p62 levels in optic nerve degeneration, which was prevented by ripasudil. p62 may correlate with autophagic flux, and decreases in its level indicate autophagy induction while increases indicate autophagy inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…[5][6][7] Some recent studies have suggested a detrimental role of p62 (SQSTM1) with regulation of autophagy in certain conditions in neurodegeneration. [8][9][10] We previously reported upregulated p62 in the optic nerve in two different models such as a hypertensive glaucoma model 11 and TNF-induced axon damage model. 12 Microtubule-associated protein light chain 3 (LC3) is distributed in autophagosomes 13 and LC3-II correlates with autophagosomes numbers.…”
mentioning
confidence: 99%
“…We conclude that a subtoxic level of a-synuclein was expressed in this study compared with previous studies in which AAV a-synuclein gene transfer did induce a lesion to the nigrostriatal system (4,5). Importantly, there were no untoward effects of expressing YFP in the Cre-targeted manner detected under these conditions because high levels of a control fluorescent protein in neurons can become toxic, as with green fluorescent protein (31,32).…”
Section: Discussionmentioning
confidence: 39%
“…Immunofluorescent or immunoperoxidase staining procedures followed previously described methods (4,31). The primary antibodies and their dilutions were as follows: anti-tyrosine hydroxylase from Pel-Freez (Rogers, AR, USA) at 1:2000; anti-a-synuclein at 1:2000 (NACP-98, kindly provided by M. Farrer, University of British Columbia, Vancouver, BC, Canada); anti-tau at 1:2000 (Tau-5, kindly provided by L. Petrucelli, Mayo Clinic, Rochester, MN, USA); and anti-TDP-43 from Abnova (Taipei, Taiwan) at 1:2000 (human TDP-43 specific).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Previous studies have suggested that protein aggregates containing endogenous p62 have a filamentous organization, e.g., in dendrites of dopaminergic neurons of mice that carry a tyrosine hydroxylase (TH) cell-specific deletion of Atg7 ( Atg7 f/f ;TH-IRES-Cre ) [ 43 ]. However, only recently evidence from studies involving recombinant p62 in vitro [ 55 , 56 ] and recombinant p62 expressed by an adeno-associated virus vector injected into the rat substantia nigra [ 57 ] have suggested that p62 itself is sufficient to form filaments. The structure and the dimensions of the p62 filaments in neurons and neuroepithelial cells of Atg7 f/f Tyr-Cre mice is similar or identical to those reported for pure p62 [ 55 ] indicating that endogenous p62 is the main, if not the only, component of these filaments.…”
Section: Discussionmentioning
confidence: 99%